A case report of a giant ileocecal cystic prolapse through the anus and literature review - Zong, Beige; Xiao, Xia; Deng, Nijiao; Wang, Wenjing; Peng, Li; Fang, Dianliang; Wang, Haoyu; Hu, Song; Li, Zhongfu; Zhang, Xin (Frontiers in Medicine, 2024)
Intussusception refers to the invagination of a proximal loop of the bowel into an adjacent distal segment. This condition is rare in adults, especially when it involves a complete folding of the ileocecal area out of the body cavity. Meanwhile, enterogenous cysts are congenital malformations that are largely identified in childhood following symptoms of bowel obstruction. While surgical treatment is ultimately required for both diseases, deciding on the type of surgery and the right time to operate can be a challenge for clinicians. It is especially difficult to decide on treatment for an adult with the coincidental occurrence of both conditions and no definitive pathologic diagnosis prior to surgery. Here, we present the case study of a 19-year-old female patient who presented with a prolapsed anus due to intussusception caused by a large ileocecal mass. The patient was admitted to the emergency department with a “massive anal mass.” She remained symptomatic after receiving conventional conservative treatment and had to undergo emergency surgery after developing an intestinal obstruction. While the patient’s intraoperative condition also confirmed the preoperative CT findings, the situation became more complicated during surgery. The postoperative pathological report indicated the presence of an enterogenous cyst. After recovery from surgery, the patient was successfully discharged. Intussusception or intestinal obstruction caused by an intestinal mass is a surgical indication, and removal is the only way to cure the condition. This case study provides a helpful reference for general surgeons, especially anorectal surgeons, imaging physicians, and pathologists, and informs the diagnosis and treatment of this patient population.